Biosorption of high-concentration Cu (II) by periphytic biofilms and the development of a fiber periphyton bioreactor (FPBR). (January 2018) - Liu, Junzhuo; Wang, Fengwu; Wu, Wantong; Wan, Juanjuan; Yang, Jiali; Xiang, Sulin; Wu, Yonghong
Highlights: Periphyton could effectively entrap high-concentration Cu-hydrate (≤20 mg L −1 ). Adsorption is the main Cu removal pathway from water by species-rich periphyton. EPS overproduction and porous structure of periphyton extended binding sites for Cu. Cu adsorption onto periphyton fits well with the pseudo-second-order kinetic model. Abstract: In this study, a kind of microbial aggregates: periphytic biofilms were used for Cu removal and immobilized onto fiber for developing a novel bioreactor. Results show that periphyton can effectively entrap Cu at initial concentrations of 2–20 mg L −1 due to the overproduction of EPS and porous structure of periphyton, and biosorption was the primary mechanism of Cu removal. Cu (mainly Cu3 (OH)4 2+, Cu2 (OH)2 2+ and Cu 2+ ) adsorption onto periphytic biofilms followed the pseudo-second order kinetic model. The biosorption process fitted the Freundlich, Langmuir and Dubinin-Radushkevich Isotherm models well and was thermodynamically spontaneous. The fiber substrate used in the periphyton bioreactor greatly increased the Cation Exchange Capacity (CEC) of the system. This study indicates that immobilization of periphytic biofilms onto fiber for novel bioreactor development is a feasible way of entrapping high-concentration Cu from wastewater.